Optimizing student writing performance in higher education: A quantitative study of teacher feedback and classroom environment - Musril Zahari; Arita Marini; Desy Safitri; Leola Dewiyani; Uyu Muawanah (Social Sciences and Humanities Open)
This study addresses the challenge of enhancing students' writing skills, specifically within the context of Indonesian higher education. The focus of this research is to examine the effect of teacher feedback on students' writing abilities and the mediating role of the classroom environment in this relationship. A quantitative approach with a correlational research design was employed, involving data collection from 244 university students enrolled in writing courses at Universitas Negeri Jakarta. The study utilized three questionnaires: Teacher's Feedback, Classroom Environment, and Writing Skills. Data were analyzed using SmartPLS with second-order analysis to explore both direct and indirect effects. The key findings indicate that teacher feedback significantly improves both the classroom environment and students' writing skills, with the classroom environment acting as a crucial mediator in this relationship. Specifically, effective teacher feedback enhances the emotional climate and student interactions, which in turn further improves writing performance. This research contributes to the literature by emphasizing the interconnectedness of teacher feedback, classroom dynamics, and student outcomes, particularly in the Indonesian context. It highlights the importance of fostering positive classroom environments to optimize the effectiveness of teacher feedback, offering valuable insights for educators seeking to enhance students' writing competencies. These findings may be of interest to educators, policymakers, and researchers aiming to improve writing instruction and educational practices.